The efferocytosis dilemma: how neutrophil extracellular traps and PI3K/Rac1 complicate diabetic wound healing - Yulin Xie; Jiaman Yang; He Zhu; Rongya Yang; Yunlong Fan (Cell Communication and Signaling)
Abstract Aims/hypothesis The resolution of apoptotic cells (ACs) is crucial for wound healing and tissue remodeling and is often impaired by persistent inflammation. This study aimed to elucidate the impact of neutrophil extracellular traps (NETs) on diabetic wound healing by targeting the phosphoinositide 3-kinase/Ras-related C3 botulinum toxin substrate 1 (PI3K/Rac1) signaling pathway, which is pivotal for macrophage efferocytosis. Methods A streptozotocin-induced diabetic mouse model was used to assess the impact of NETs on efferocytosis in vivo. The effects of NETs on macrophage efferocytosis and wound healing were evaluated using specific inhibitors and agonists targeting the PI3K/Rac1 pathway. In vitro, macrophages from diabetic wounds or cell lines (Raw264.7) were treated with NETs and a panel of pharmacological agents of the PI3K/Rac1 pathway to evaluate macrophage efferocytosis. Results NETs were found to inhibit macrophage efferocytosis, resulting in delayed clearance of ACs that accumulate within the wounds. Inhibition of NET formation in diabetic mice rescued impaired efferocytosis, accompanied by reactivation of PI3K and Rac1 in macrophages. Moreover, pharmacological agents targeting the PI3K/Rac1 pathway restored NETs-induced impairment in efferocytosis, leading to rapid wound healing. Raw264.7 cells exhibited elevated activation levels of PI3K and Rac1 when co-cultured with ACs in vitro. Nevertheless, this signaling activation was inhibited when cultured in a NETs-conditioned medium, leading to attenuated efferocytosis. Conclusions/interpretation Targeting NETs and the PI3K/Rac1 pathway emerges as a potential therapeutic strategy to enhance healing in diabetic wounds by promoting macrophage efferocytosis.